Model bimbingan kelompok dengan teknik bermain peran untuk meningkatkan keterampilan sosial - Muhammad Junaedi Mahyuddin (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2016)
This study aims to: (1) know the description of how to do the group guidance, (2) know the students social skills, (3) create a group guidance model using role play technique to increase the students social skills. The methodoogy applied in the study is Research and Development (R&D). The population of the study is the students of Grade 5 Athirah Primary School Makasssar which is 62 stduents. The technique sampling used in the study is purposive sampling which is applied to 8 of the students. The result of the wilcoxon statistic test shows that group guidance model using role play technique is effective to increase students social skills. The study suggests the teacher especially guidance and counseling teacher to optimalize the application of group guidance service using role play technique that function as the tool to help students to increase their social skills.